A COMPREHENSIVE INVENTORY AND ECOLOGICAL ASSESSMENT OF ALIEN PLANT INVASION IN MIZORAM, INDIA - Rabishankar Sengupta; Sudhansu Sekhar Dash (Indonesian Journal of Forestry Research, 2020)
Invasion by alien plants has a detrimental effect on the natural forest plant community, leading to the loss of native species. An inventory of alien plants facilitates in determining the potential threats to the natural plant biodiversity. This present paper evaluates the alien plants in Mizoram (an Indo-Burma hotspot region) and provides the first authentic inventory of alien plants of Mizoram along with their diversity, ecological aspects, origin, and status of invasion. Extensive field surveys were done during July 2018 to September 2019 in different protected areas of Mizoram.  We adopted Random Sampling Technique using nested quadrats in a plot size of 400 m2 (20 m × 20 m), within which a quadrate size of 5 m × 5 m was laid for shrubs and 1 m × 1 m was laid for herbs. Plant specimens were collected, dried, poisoned with 0.1% Mercuric Chloride (MgCl2); voucher specimens were prepared and deposited in Central National Herbarium, Botanical Survey of India (CAL) after proper identification.The results revealed the occurrence of 163 alien plant species under 135 genera belonging to 51 families in Mizoram.  Maximum species were represented by family Asteraceae with 29 species followed by Leguminosae (19 species), Convolvulaceae (9 species), Euphorbiaceae (7 species) and Amaranthaceae (7 species). The 57.66% of the alien species reported from Mizoram were of American origin followed by 11.65 % from African, 7.36% from Mexican and 5.52% from Australian origin. Life form analysis revealed the presence of 58.64 % herbs, 15.43 % trees and 9.87% shrubs. Out of the whole alien plants recorded, 91 species used in traditional medicines, 43 species as ornamental, 15 species were edibles, nine species used as timber and four species used as green manure. The study also recommends the ten most obnoxious species, five neo-invasive plants, which have the greatest potential threats to the native flora. The process and probable causes of invasion in the state were also discussed briefly, which may be utilized in the preparation of conservation or forest management policies.